Дослідження архітектурних підходів до проектування мало-функціональних веб-додатків на платформі .net - Юдін, І. О. (ХНУРЕ, 2024)
This research focuses on analyzing architectural approaches for developing small objects, implementing optimal strategies, among monolithic, microservices, Cloud-Native, and event-driven serverless architectures. Points of strength, productivity and cost-effectiveness often need to be considered, which are important to achieve maximum efficiency for small projects. Select the right architecture that plays a critical role in simplifying operations, speeding up and scaling stalls, while not considering high performance and reducing costs.
Keywords: веб-додаток; платформа .NET